2004
DOI: 10.1073/pnas.0407280102
|View full text |Cite
|
Sign up to set email alerts
|

The modular architecture of protein–protein binding interfaces

Abstract: Protein-protein interactions are essential for life. Yet, our understanding of the general principles governing binding is not complete. In the present study, we show that the interface between proteins is built in a modular fashion; each module is comprised of a number of closely interacting residues, with few interactions between the modules. The boundaries between modules are defined by clustering the contact map of the interface. We show that mutations in one module do not affect residues located in a neig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
282
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(295 citation statements)
references
References 35 publications
11
282
1
1
Order By: Relevance
“…These findings show that the modular distribution of hot spots in binding sites relates to binding specificity. Thus, despite the complexity of mechanisms by which binding sites modulate binding affinity and specificity for biological function, consistent with experimental data [25], it appears that the modular distribution of hot spots plays a major role in achieving this goal. This binding site architecture might have been designed by evolution to generate a wide range of binding affinities and specificities.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…These findings show that the modular distribution of hot spots in binding sites relates to binding specificity. Thus, despite the complexity of mechanisms by which binding sites modulate binding affinity and specificity for biological function, consistent with experimental data [25], it appears that the modular distribution of hot spots plays a major role in achieving this goal. This binding site architecture might have been designed by evolution to generate a wide range of binding affinities and specificities.…”
Section: Discussionsupporting
confidence: 66%
“…Alanine scanning analysis has revealed that some binding hot spots are conserved within protein families [19], whereas others are specific to each family member [20][21][22]. Experiments have emphasized the modular design of binding sites, with energetic cooperative contribution of single residues within the module; and additive between modules [23][24][25]. Computational protein design methods have also been used to elucidate the tradeoff between stability and specificity for the optimization of biological function [8,26].…”
Section: Introductionmentioning
confidence: 99%
“…A hypothesis that is very similar to the one analyzed here has been first proposed by Reichmann et al (27) to quantify the nonadditivity of changes in binding energies between protein-protein interfaces. In Ref.…”
Section: Introductionsupporting
confidence: 68%
“…In Ref. (27), this hypothesis was confirmed experimentally on the example of the interaction between TEM1-β-lactamase and β-lactamase inhibitor protein.…”
Section: Introductionmentioning
confidence: 79%
“…Reichmann et al (40) have recently suggested that protein-protein binding sites have a modular architecture made up of clusters of residues with both strong intracluster connections and weak intercluster connections. The deletion of a whole cluster of residues has no impact on the structure of the interface, whereas single mutations within a given cluster may lead to the structural rearrangement of their cluster.…”
Section: Cluster Analysis Reveals the Differential Contributions Of Tmentioning
confidence: 99%